I am the Hulk - Figueroa, Acton; McKelvey, Shawn; Schamus, James, 1959- (New York : HarperFestival, 2003)
Life isn't easy for Bruce Banner. He used to be a scientist. Now, as the Hulk, he's become an experiment. Scientists study him. Soldiers pursue him. But nothing can stop the Hulk!
"Now a major motion picture from Universal Pictures"--Cover.
At head of title: Hulk.
4-7.
Keywords: Heroes -- Juvenile fiction; Metamorphosis -- Juvenile fiction; Incredible Hulk (Fictitious character) -- Juvenile fiction; Science fiction